Precision agriculture monitoring system using wireless sensor network and Raspberry Pi local server - Flores, Kristoffer O (Archīum Ateneo, 2017)
Precision Agriculture is utilized to improve the productivity and efficiency of limited agricultural resources by monitoring the relevant data in the field. The main objective of this study is to deploy a low-cost sensor system, gather field data, and display the data through a graphical user interface (GUI). Sensors such as humidity, temperature, moisture, luminosity, electrical conductivity, and pH was used for data acquisition and the Raspberry Pi, acting as a local server, was used for data processing and transfer. The data sent was stored in a main server and organized using SQL. A GUI was developed to provide visualization of the data gathered. The trends of data gathered revealed pattern such as the occurrence of a local maximum for humidity right after dawn and the inverse relationship of humidity and temperature. The whole system was tested and proven to work by the application of fertilizer to the soil and seeing its response in the GUI.